Fast fabrication of freestanding MXene-ZIF-8 dual-layered membranes for H2/CO2 separation - Hong, Xilu; Lu, Zong; Zhao, Yali; Lyu, Luxi; Ding, Li; Wei, Yanying; Wang, Haihui (Journal of membrane science, 2022)
As one of the green, renewable, and clean energy resources, hydrogen is widely developed and utilized throughout the world. Highly efficient membrane separation for hydrogen production is required to give promising gas permeance with enough H2 selectivity. The membranes are desired to be produced in large-scale, fast and facile methods. Here we report for the first time a kind of freestanding MXene-ZIF-8 dual-layered membrane for hydrogen separation. Fast synthesis of such membranes is realized by combining electrophoretic deposition (EPD) and fast current-driven synthesis (FCDS), achieving the assemble of MXene layer and growth of ZIF-8 layer, respectively, overcoming the traditional time-consuming vacuum filtration methods and solvothermal synthesis. The MXene-ZIF-8 dual-layered membrane prepared within 20 min exhibits significantly improved gas separation performance, whose H2/CO2 selectivity increases from 44 for the pristine MXene membrane to 77 with H2 permeance of 5.97 × 10−8 mol m−2 s−1 Pa−1. This concept of structure design of membrane can also be extended to other dual-layered membranes, including various 2D nanosheet layers combined with different MOF layers. [Display omitted] •Freestanding MXene-ZIF-8 dual-layered membrane was prepared by EPD/FCDS in 21 min.•It exhibits high separation performance for H2/CO2 with selectivity of 77.•A MXene-ZIF-8 dual-layered membrane with large area of 525 cm2 was prepared.